Relation of Temperature Changes in Asphalt Pavements to Pavement Bearing Capacity Evaluation - Komacka, Jozef; Korenko, Martin; Piala, Jaroslav (Communications - Scientific letters of the University of Zilina, 2007)
Temperature changes in asphalt pavements have to be taken into account at the diagnostic and evaluation process of pavements bearing capacity. Theoretical calculations resulting from general theory are not suitable for the practical use. Therefore the experimental test section with flexible and semi-rigid pavement was built and the temperatures were measured at different depths. The examples of typical temperature gradients for the hot summer and cold spring day are presented and their similarities are stated. The development of the simple method for the determination of mean temperature of pavement asphalt layers is described and the correction values relative to the temperature of pavement surface are shown for the time interval from 2000 to 800 and the asphalt layers thickness of 210 mm.